Genome‐scale RNA interference screen identifies antizyme 1 (OAZ1) as a target for improvement of recombinant protein production in mammalian cells. Issue 11 (21st September 2016) - Xiao, Su; Chen, Yu Chi; Buehler, Eugen; Mandal, Swati; Mandal, Ajeet; Betenbaugh, Michael; Park, Myung Hee; Martin, Scott; Shiloach, Joseph
ABSTRACT: For the purpose of improving recombinant protein production from mammalian cells, an unbiased, high‐throughput whole‐genome RNA interference screen was conducted using human embryonic kidney 293 (HEK 293) cells expressing firefly luciferase. A 21, 585 human genes were individually silenced with three different siRNAs for each gene. The screen identified 56 genes that led to the greatest improvement in luciferase expression. These genes were found to be included in several pathways involved in spliceosome formation and mRNA processing, transcription, metabolic processes, transport, and protein folding. The 10 genes that most enhanced protein expression when downregulated, were further confirmed by measuring the effect of their silencing on the expression of three additional recombinant proteins. Among the confirmed genes, OAZ1 —the gene encoding the ornithine decarboxylase antizyme1—was selected for detailed investigation, since its silencing improved the reporter protein production without affecting cell viability. Silencing OAZ1 caused an increase of the ornithine decarboxylase enzyme and the cellular levels of putrescine and spermidine; an indication that increased cellular polyamines enhances luciferase expression without affecting its transcription. The study shows that OAZ1 is a novel target for improving expression of recombinant proteins. The genome‐scale screening performed in this work can establish the foundation for targeted design of an efficient mammalian cell platform for various biotechnological applications. Biotechnol. Bioeng. 2016;113: 2403–2415. © 2016 Wiley Periodicals, Inc. Abstract : Improving recombinant protein production from mammalian cells for research and therapeutic purposes is of major interest. For identifying unknown genes and pathways useful for improving protein expression, the effect of non‐coding RNA, both miRNA and siRNA, on recombinant protein expression in 293HEK cells was investigated by applying large scale screening of miRNA and siRNA. Screening of 21, 585 genes led to the selection of OAZ1, a gene that encodes ornithine decarboxylase antizyme, as a potential target since its silencing enhanced recombinant protein expression without affecting cell viability. Further studies revealed that silencing OAZ1was associated with increased concentration of polyamines.